The hangover [videorecording (DVD)] - Phillips, Todd, 1970-; Cooper, Bradley; Helms, Ed; Galifianakis, Zach; Graham, Heather, 1970-; Bartha, Justin; Tambor, Jeffrey, 1944- (distributed by Warner Home Video, 2009)
Doug Billings and Tracy Garner are about to get married. Two days before the wedding, Doug and his groomsmen hop into Tracy's father's Mercedes for a 24-hour stag party in Las Vegas. The morning after their arrival in Vegas, they awaken in their Caesars Palace hotel suite each with the worst hangover. No one remembers what happened in the past twelve or so hours. The suite is in shambles and Doug is missing. Phil, Stu and Alan try to find Doug using only what little pieces of information they have at hand and go on a journey of discovery. However, it's a race against time since they need to find Doug and get him back to Los Angeles in time for the wedding.